Persepsi Mahasiswa Terhadap Mutu Tes Hasil Belajar Buatan Dosen - Yudha Nata Saputra (AL-MURABBI: Jurnal Studi Kependidikan dan Keislaman, 2022)
The purpose of this study is to analyze student opinions on the quality of learning outcomes tests made by lecturers. This research is a survey research conducted on 83 students. The criteria for the quality of the learning outcomes tests examined in this study include the compatibility of the tests with the instructional objectives that have been set, the representation of material / learning outcomes in the learning outcomes test prepared by the lecturer, the congruence of the test items with the measured learning outcomes, the suitability of the purpose of using the learning outcomes test, the lectures’ ability in making a reliable test and interpreting it to create student activities for learning. The results of the study showed that the quality of the learning outcomes tests made by lecturers obtained an average score of 79.93 which was still included in the medium category. Among the six quality criteria studied, the learning outcomes test criteria made by the lecturer according to their intended use obtained the highest percentage (27.7%), while the item suitability criteria with the learning outcomes test to be measured obtained the lowest percentage (4.8%). Tujuan dari penelitian ini, yaitu untuk menganalisa pendapat mahasiswa terhadap mutu tes hasil belajar yang dibuat oleh dosen. Penelitian ini merupakan penelitian survey yang dilakukan kepada 83 mahasiswa. Kriteria mutu tes hasil belajar yang diteliti dalam penelitian ini, meliputi kesesuaian tes hasil belajar yang dibuat dengan tujuan instruksional yang telah ditetapkan, keterwakilan materi/hasil belajar dalam tes hasil belajar yang disusun dosen, kesesuaian item-item tes hasil belajar dengan hasil belajar yang hendak diukur, kesesuaian tujuan penggunaan tes hasil belajar, kemampuan dosen dalam membuat tes hasil belajar yang reliabel dan menafsirkannya, kemampuan tes hasil belajar yang dibuat untuk membuat aktivitas mahasiswa untuk belajar. Hasil penelitian menunjukkan bahwa mutu tes hasil belajar yang dibuat dosen memperoleh skor rata-rata 79.93 yang masih termasuk dalam kategori sedang. Di antara ke enam kriteria mutu yang diteliti, kriteria tes hasil belajar yang dibuat dosen sesuai dengan tujuan penggunaannya memperoleh presentase tertinggi (27.7%), sementara kriteria kesesuaian item dengan tes hasil belajar yang hendak diukur memperoleh presentase terendah (4.8%).